2016
DOI: 10.3171/2015.4.spine14944
|View full text |Cite
|
Sign up to set email alerts
|

Anterior corpectomy via the mini-open, extreme lateral, transpsoas approach combined with short-segment posterior fixation for single-level traumatic lumbar burst fractures: analysis of health-related quality of life outcomes and patient satisfaction

Abstract: OBJECT The authors present clinical outcome data and satisfaction of patients who underwent minimally invasive vertebral body corpectomy and cage placement via a mini-open, extreme lateral, transpsoas approach and posterior short-segment instrumentation for lumbar burst fractures. METHODS Patients with unstable lumbar burst fractures who underwent corpectomy and anterior column reconstruction via a mini-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
3
35
0
2
Order By: Relevance
“…To overcome the disadvantages of anterior-only and posterior-only approach, many authors have reported satisfactory results with a combined anterior-posterior approach [8][9][10][11]. However, it was generally believed that the conventional combined anterior-posterior approach has more surgical invasiveness and morbidity than those of an anterior-only or posterior-only approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the disadvantages of anterior-only and posterior-only approach, many authors have reported satisfactory results with a combined anterior-posterior approach [8][9][10][11]. However, it was generally believed that the conventional combined anterior-posterior approach has more surgical invasiveness and morbidity than those of an anterior-only or posterior-only approach.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous minimally invasive combined posterior-anterior techniques have attempted to decrease the associated morbidity. These have included combining vertebral augmentation with pedicle screw instrumentation [5,6], transpedicular corpectomy with expandable cage combined with pedicle screw fixation [7], and minimally invasive corpectomy and posterior pedicle instrumentation [8,9]. However, the optimal surgical treatment strategy for unstable thoracolumbar burst fractures remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In fact the risk of another vertebral fracture increases 5-fold after the first event ('domino-effect'). These conditions must be considered in case of an open approach, especially in order to identify the correct level to treat and to select the appropriate surgery instrumentation, because in this cases there is and high risk of fixation failure (4)(5)(6). In this case, probably, the ability of the vertebral body to fuse itself, induced by the Ankylosing Spondylitis, prevailed on the worsening of the fracture, reaching a balance and obtaining a natural resolution.…”
Section: Discussionmentioning
confidence: 99%
“…These complications included durotomies, intercostal neuralgia, deep venous thrombosis, pleural effusion, hemothorax, wound infection and hardware failure. Another study focusing on corpectomies for unstable lumbar burst fractures in 12 patients showed that when supplemented with short-segment posterior fixation this approach improved local lordosis, had good patient satisfaction outcomes and was tolerated well with minimal pain and morbidity (45). In their series, three of the patients required a chest tube for pleural violation and 1 patient required reoperation for cage subsidence/hardware failure.…”
Section: Clinical Experience With Minimally Invasive Corpectomies Formentioning
confidence: 99%